Scanpaths of Complex Image Viewing: Insights From Experimental and Modeling Studies. (August 2015) - Samarin, Anatoly; Koltunova, Tatiana; Osinov, Vladislav; Shaposhnikov, Dmitry; Podladchikova, Lubov
From the first works of Buswell, Yarbus, and Noton and Stark, the scan path for viewing complex images has been considered as a possible key to objective estimation of cognitive processes and their dynamics. However, evidences both pro and con were revealed in the modern research. In this article, the results supporting the Yarbus-Stark concept are presented. In psychophysical tests, two types of images (three paintings from Yarbus` works and four textures) were used with two instructions, namely, "free viewing" and "search for modified image regions." The focus of the analysis of experimental results and modeling has been given to local elements of the scan path. It was shown that each parameter used (square of viewing area, S ; distance between center of mass of viewing area and image center, R ; parameter X i, based on duration of the current fixation and angle between preceding and following saccades), reflects the specificity of both visual task and image properties. Additionally, the return gaze fixations which have a set of specific properties and mainly address to the areas of interest on image were revealed. Evidently these facts can be formalized in an advanced mathematical model as additional instrument to study the mechanisms of complex image viewing.